The role of Islamic spiritual extracurricular activities in developing Islamic religious consciousness at vocational school - Aprilianti, Vika; Ajahari, Ajahari; Surawan, Surawan (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
Islamic Spiritual Extracurricular at SMKN 3 Palangka Raya plays an important role in shaping the character of students who are noble and have high religious consciousness. Through various activities organized, such as Islamic studies, tadarus Al-Quran, and social activities, students are invited to explore the values of Islamic teachings and implement them in everyday life. This study aims to analyze the effect of Rohis extracurricular activities on increasing students' religious consciousness at SMKN 3 Palangka Raya and to determine students' interest in participating in activities in Islamic Spiritual Extracurricular Activities. The research method used is descriptive quantitative with data collection through observation, interviews, and documentation. The results showed that: 1) Islamic Spiritual Extracurricular includes, a) Islamic Boarding School, b) Worship Training, c) Tilawah & Tahsin Al-Qur'an, d) Commemoration of holidays, e) Habsyi. 2) Islamic Spiritual Extracurricular at SMKN 3 Palangka Raya can make a very good contribution, while the contribution is (83.59%) which consists of affective aspects of 83.45% (very good), cognitive aspects of 84.17% (very good), psychomotor aspects of 85.15% (very good) in increasing students' religious consciousness.